Tindak Tutur Direktif dalam Komik Kisah Petualangan Kyai Sadrach (Directive Speech Acts in the Comic The Adventure Story of Kyai Sadrach). - Prasetyo, Chrisnatama Tangguh; Annisa, Luthf (Universitas Sebelas Maret, 2026)
This study aims to analyse directive speech acts found in the comic Kisah Petualangan Kyai Sadrach. This research employs a qualitative descriptive approach with a pragmatic perspective. The data source of this study is the dialogue between characters in the comic Kisah Petualangan Kyai Sadrach. The data consist of utterances containing directive speech acts collected through reading and note-taking techniques. The analysis is based on the classification of directive speech acts proposed by Searle and Vanderveken (1989). The results show that there are 55 directive utterances classified into 10 types of directive speech acts, namely requesting, asking, commanding, prohibiting, suggesting, ordering, warning, advising, praying, and pleading. Among these types, asking is the most dominant directive speech act with a percentage of 52,7%, indicating that the characters frequently use questions to obtain information and clarify situations within the narrative. The variety of directive speech acts demonstrates how the characters use language to influence the actions of other characters and develop interactions within the storyline.